SAT0308 Effective Suppression of Adp-Dependent Platelet Activation by Clopidogrel May Result in Clinical Stabilization in Patients with Systemic Sclerosis. Results of an Open Label, Proof of Concept Study. (10th June 2014) - Delis, K.; Daoussis, D.; Gizas, V.; Davlouros, P.; Alexopoulos, D.; Andonopoulos, A.P.
Abstract : Background: Even though systemic sclerosis (SSc) is the prototype fibrotic disease the primary event in the pathophysiology is thought to be vasculopathy. It is currently unknown what links vascular disease to fibroblast activation in SSc. Evidence suggests that platelets are not just cell fragments that participate in thrombus formation but are active players in vascular disease. Recent experimental data indicate that activated platelets release serotonin that binds 5-HT2B receptor on fibroblasts leading to fibroblast activation and increased collagen production. Clopidogrel, an inhibitor of the P2Y12 ADP receptor, was shown to prevent fibrosis in several animal models of SSc Objectives: To assess the effect of clopidogrel treatment in patients with SSc on i) ADP-dependent platelet activation, ii)plasma serotonin levels and iii) clinical outcomes Methods: We recruited 14 patients with SSc and 8 patients with rheumatoid arthritis as controls. Platelet activation was assessed by Multiplate (Roche), prior to and following 10 days of clopidogrel treatment (75 mg daily). At the same time points serotonin was measured in platelet poor plasma by RIA. Patients were evaluated at baseline and following 6 and 12 months of clopidogrel treatment. No changes in background treatment was allowed during the study Results: Most patients with SSc were female (n=13), had limited disease (n=11) with a mean age (±SEM) of 63.5 (±3.2) years and disease duration of 11 (±1.4) years. Three patients were receiving MMF, 4 rituximab and 4 bosentan but had been on that treatment for at least 3 years prior to enrollment. Platelets were highly activated in patients with SSc with 6 patients (42.8%) showing high platelet reactivity (>468 AU/min) in sharp contrast to only 1 patient (12.5%) in the RA group. Clopidogrel treatment significantly reduced platelet reactivity in patients with SSc (mean ± SEM AU/min: 364.9±60.5 vs 160.6±47.9, prior to and following treatment respectively, p=0.02) but not in patients with RA (mean ± SEM: 292.8±76.3 vs 250.6±118.9, p=0.5). Plasma serotonin levels did not change following treatment (mean ± SEM ng/ml: 182±16 vs 206±26, p=0.4). PFTs remained stable at 12 months compared to baseline (mean ± SEM of FVC%: 91±5 vs 98±9 and mean ± SEM of DLco%: 65±4 vs 57±7 at baseline vs 1-year respectively, p=ns in both cases). Other indices of internal organ function (eGFR, RVSP) remained stable. Skin thickening as assessed by MRSS improved (p=0.01); S-HAQ decreased but not to the level of statistical significance (p=0.08). No side effects related to the use of clopidogrel were recorded Conclusions: Clopidogrel effectively suppresses ADP-dependent platelet activation in patients with SSc and may result in clinical stabilization. Taking into account the progressive nature of the disease, stabilization could be interpreted as a positive outcome. Further exploration of the potential role of clopidogrel as an adjunct therapy for SSc is needed. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4093